2016
DOI: 10.1186/s13229-016-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, but not autism spectrum disorder, may be related to the production of emotional facial expressions

Abstract: BackgroundA prominent diagnostic criterion of autism spectrum disorder (ASD) relates to the abnormal or diminished use of facial expressions. Yet little is known about the mechanisms that contribute to this feature of ASD.MethodsWe showed children with and without ASD emotionally charged video clips in order to parse out individual differences in spontaneous production of facial expressions using automated facial expression analysis software.ResultsUsing hierarchical multiple regression, we sought to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 61 publications
5
64
0
Order By: Relevance
“…Such technologies are already being developed and made commercially available (e.g. the Affective and Emotient Modules from iMotions () biometric platform), which has been modified from earlier versions of the software [Littlewort et al, ] and has been used in one study analyzed in the present meta‐analysis (see, Trevisan et al, ). This technology was originally developed based on the facial action coding system (FACS; Ekman & Friesen, ; Ekman et al, ), a taxonomy of human facial movements that in various combination represent different emotional facial expressions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such technologies are already being developed and made commercially available (e.g. the Affective and Emotient Modules from iMotions () biometric platform), which has been modified from earlier versions of the software [Littlewort et al, ] and has been used in one study analyzed in the present meta‐analysis (see, Trevisan et al, ). This technology was originally developed based on the facial action coding system (FACS; Ekman & Friesen, ; Ekman et al, ), a taxonomy of human facial movements that in various combination represent different emotional facial expressions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research has shown that higher degrees of alexithymia (i.e. difficulties identifying and describing one's own emotions) in participants with ASD is associated with reduced spontaneous production of facial expressions, and also associated with poorer recognition of others' emotions [Brewer et al, ; Trevisan et al, ]. In addition, clinical depression is often accompanied by severe forms of apathy with little emotional reaction to positive or negative events, which contributes to the expression of flat affect [Mayer, Alpert, Stastny, Perlick, & Empfield, ; Starkstein, Ingram, Garau, & Mizrahi, ; Trémeau et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Production of emotional facial expressions has also been shown to be affected in alexithymic individuals, and reduced emotional expression has been linked to alexithymic traits rather than autistic traits in groups with and without autism McDonald & Prkachin, 1990;Trevisan, Bowering, & Birmingham, 2016). Limited or abnormal facial expressions and eye contact may thus be a feature of alexithymia and contribute to higher scores on these ADOS items, increasing the likelihood of a diagnosis.…”
Section: Alexithymia and The Social Affect Ados Subscalementioning
confidence: 99%
“…In both ASD and Alexithymia there are thought to be widely overlapping difficulties related to social skills and emotional competence [5]. It has also been shown that Alexithymia, rather than ASD, predicted a lack of expressive response to emotionally charged stimuli [6]. Alexithymia is thought to arise as there is impaired interoception (the ability to perceive the internal state of one's body) and it had been shown that these signals have less impact upon decision making in those with Autistic Spectrum [7].…”
Section: Discussionmentioning
confidence: 99%